Impaired FGF10 Signaling and Epithelial Development in Experimental Lung Hypoplasia With Esophageal Atresia - Jun Wang; Jun Wang; Hao Liu; Linlin Gao; Xiaomei Liu (Frontiers Media S.A., 2018)
Patients with esophageal atresia (EA) and tracheoesophageal fistula (TEF) often experience persistent respiratory tract disease. In experimental models, doxorubicin-induced developmental lung abnormalities may result from downregulation of branching morphogenesis factor fibroblast growth factor (Fgf10). This study investigated the temporospatial expression of Fgf10 pathway components and lung epithelial factors in an doxorubicin-induced EA-TEF model by quantitative polymerase chain reaction, immunohistochemistry, and immunoblotting. Epigenetic regulation of gene expression by histone deacetylation was also investigated. Bone morphogenetic protein (Bmp) 4 and Cathepsin H (Ctsh), downstream targets of Fgf10, were significantly downregulated in the EA-TEF model during the saccular stage, consistent with Fgf10 expression. The developmental expression pattern of P2x7 receptor (ATI-cell marker), Sftpa, and Sftpb in lung epithelial cells was not affected. Sftpc (ATII-cell Marker) and Scgb1a1 (Clara cell marker) were significantly downregulated at the canalicular stage. Meanwhile, histone deacetylase (Hdac) 1 was upregulated and subsequently decreased acetylation of histone H3 Lys56 in the EA-TEF model, which returned to a normal level at the saccular stage. In conclusion, disturbed molecular signaling involving Fgf10/Ctsh was associated with impaired airway branching and epithelial cell development in lung morphogenesis, as evidenced by downregulated Sftpc and Scgb1a1 protein expression. The influence of Hdac1 activity on gene and protein expression in lung epithelial cells deserves further study.